Decolourization Of Brilliant Green Dye In Aqueous Media By Using Modified Mof-5 Adsorbent - Razaman, Noor Suhaila (Universiti Sains Malaysia, 2022)
This research is mainly about the decolourization of brilliant dye by using different type of modified adsorbent, pristine Metal Organic Framework (MOF-5), MOF-5 coated with coal fly ash (CFA) from factory, MOF-5 coated with rice husk ash (RHA) from factory, MOF-5 coated with RHA900, MOF-5 coated with RHA500, as well as MOF-5 coated with different ratio of mixed RHA900 and raw CFA from factory. The synthesized adsorbents were used for adsorption study at different contact time, adsorbent amount and initial dye concentration but constant shaking rate (200 rpm) and temperature (30 ⁰C). Modified metal organic framework (MOF-5) coated with RHA900 has a higher adsorption capability towards the brilliant green (BG) dye. A high removal of BG dye which is about 92% could be occurred by using 1.4 g of MOF-5@RHA900 adsorbent shaking time of 2 hours. The removal of BG dye increases with the increasing of contact time, decreasing initial dye concentration and increasing of adsorbent amount. The kinetic of the adsorption was compared based on pseudo-first-order and pseudo-second-order models while the isotherm was analyzed based on Langmuir and Freundlich models. Both kinetic and isotherm model were choose based on the best fitted adsorption data. The adsorption kinetic obeyed the pseudo-second-order model while the adsorption isotherm followed the Langmuir Isotherm model. The characterization of the prepared and spend modified MOF-5 adsorbents were analyzed by using X-ray diffraction (XRD) to identify structure of the crystal, scanning electron microscope (SEM) to study the shapes and morphologies, Brunauer-Emmet-Teller (BET) to identify physical properties and FT-IR test to identify the changes of the functional group. MOF-5@RHA900 adsorbent has a higher BET surface (91.6810 m2 g-1) compared to MOF-5@CFAf (3.4651 m2 g-1), which could allow higher rate of BG dye removal. The mesopore structure of MOF-5@RHA900 and MOF-5@CFAf adsorbent had been proved by the analysis of pore distribution.